A Worldwide Health Problem: Parental Alienation - Boch-Galhau, Wilfrid von (Highlights on Medicine and Medical Science Vol. 3, 2021)
Parental Alienation is a serious mental condition that professionals who work with children, adolescents and adults should know. Parental Alienation is to be found mainly in situations of high conflict separation and divorce, however it exists also in some other contexts. In this article two case examples are presented. The first case example shows parental alienation in a high conflict divorce situation, the second demonstrates institutionally induced parental alienation as a consequence of wrong child sexual abuse accusations by a mentally ill neighbour. Although about thousand three hundred professional articles, book chapters and books, and also empirical studies, exist meanwhile (see website https://ckm. vumc.org/pasg) from all over the world there is still not enough awareness of Parental Alienation in professional practise. Parental Alienation is a child protection issue and the child protection authorities and the courts have to act accordingly.